Temperament and Character Personality Profile and Illness-Related Stress in Central Serous Chorioretinopathy - Rupert Conrad; Franziska Geiser; Alexandra Kleiman; Berndt Zur; Andrea Karpawitz-Godt (The Scientific World Journal, 2014)
Psychological stress is a risk factor as well as a consequence of central serous chorioretinopathy (CSC). Impulsiveness, overachievement, emotional instability, and hard-driving competitiveness have been discussed as personality features in CSC patients. We investigated 57 consecutive CSC patients and 57 age- and gender-matched controls by means of the Symptom Checklist 90-R and the Temperament and Character Inventory. Somatic risk factors, illness characteristics, subjective assessment of severity of illness, and illness-related stress in different areas of life (work, private life) were evaluated. CSC patients showed significantly higher emotional distress as measured by the Global Severity Index. The CSC personality was characterized by lower scoring on the character dimension cooperativeness and the temperament dimension reward dependence. Cooperativeness as well as subjective assessment of severity of CSC has been recognized as significant predictors of illness-related work stress accounting for 30% of variance. Implicating competitiveness, hostility and emotional detachment, lower level of cooperativeness, and reward dependence support the existence of specific aspects of type A behaviour in CSC patients. Low perceived social support and loss of control may explain the significant contribution of this personality dimension to illness-related work stress. Treatment of CSC should thus incorporate psychoeducation about factors contributing to illness-related stress.